2004
DOI: 10.1271/bbb.68.1125
|View full text |Cite
|
Sign up to set email alerts
|

Novel Fusicoccins R and S, and the Fusicoccin S Aglycon (Phomopsiol) fromPhomopsis amygdaliNiigata 2-A, and Their Seed Germination-stimulating Activity in the Presence of Abscisic Acid

Abstract: Our search for new 3-hydroxyfusicoccins structurally related to cotylenin A from a culture of Phomopsis amygdali Niigata 2-A resulted in the isolation of novel 3-hydroxy fusicoccins, called fusicoccins R and S, and the fusicoccin S aglycon, called phomopsiol, together with known 3 -hydroxyfusicoccin J. The structure of phomopsiol was identified as that of O-demethyl-3-epicotylenol based on spectroscopic evidence. The structures of fusicoccins R and S were also determined to be those of 3 0 -deacetyl-3 -hydroxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 10 publications
(13 reference statements)
0
8
0
Order By: Relevance
“…Furthermore, fungal endophytes such as the Ascomycete Diaporthe ( Phomopsis ) sp. produce a diversity of interesting and bioactive sesquiterpene scaffolds, such as cadinanes (Silva et al, 2006), drimanes (Zang le et al, 2012) and meroterpenoids (Hemtasin et al, 2011; Ma et al, 2015; Tajima et al, 2004) and as we have shown here, trans -humulane scaffolds. Diaporthe ( Phomopsis ) sp.…”
Section: Discussionmentioning
confidence: 66%
“…Furthermore, fungal endophytes such as the Ascomycete Diaporthe ( Phomopsis ) sp. produce a diversity of interesting and bioactive sesquiterpene scaffolds, such as cadinanes (Silva et al, 2006), drimanes (Zang le et al, 2012) and meroterpenoids (Hemtasin et al, 2011; Ma et al, 2015; Tajima et al, 2004) and as we have shown here, trans -humulane scaffolds. Diaporthe ( Phomopsis ) sp.…”
Section: Discussionmentioning
confidence: 66%
“…Compounds 2 -6 were identified as abscisic acid (2) (Jadulco et al 2002;Zheng et al 2002;del Refugio Ramos et al 2004), fusicoccin J (3) (Tajima et al 2004), 3a-hydroxyfusicoccin J (4) (Tajima et al 2004), 5-hydroxymethylmellein (5) (Kokubun et al 2003) and 4-hydroxyphenethyl acetate (6) Compounds 1 -6 were tested for antimicrobial activity against three plant pathogenic fungi: Gibberella zeae, Verticillium albo-atrum and Fusarium nivale, and two bacteria: Escherichia coli and Pseudomonas aeruginosa 2033E. The positive controls were carbendazim and gentamicin, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The untreated cultures appeared to be rich in polyketides of masses below 400 amu. While an exhaustive dereplication was not undertaken, examples of these compounds were provisionally identified as 4,6-dihydroxymellein (t R = 21.0 min), 20 patulolide C (t R = 21.5 min), 21 convolvulopyrone (t R = 24.0 min), 22 culpin (t R = 24.5 min), 23 phompsiol (t R = 28.0 min), 24 To obtain milligram quantities of the new metabolites, scale-up cultures were grown (5 × 1 L) using methods and conditions outlined in the Experimental Section. The immediate goal was to characterize the new compounds and evaluate their biological properties.…”
Section: Resultsmentioning
confidence: 99%